India–China Energy Geopolitics: Dominating Alternative Energy Market in Pacific Asia. (January 2015) - Janardhanan, Nandakumar
Energy geopolitics, marked by competition and rivalry in the global search for petroleum fuels, has been one of the defining elements in the bilateral energy engagement of India and China. In the last decade, the international energy market witnessed fierce race among the two as they competed for overseas petroleum resources. Unlike the politics over the search for petroleum resources witnessed in the last decade, the new energy geopolitics reflects the competition of these two countries as they seek to expand their influence in the alternative energy sector of the developing Asian economies. Investment, technology transfer and aid to develop new energy resource are some of the key economic and diplomatic tools the two countries use to expand their reach. This article focuses on the Sino-Indian competition in the alternative energy space in developing Asia, and aims to understand the level of success the two countries witness in this emerging geopolitical engagement.